KOMUNIKASI PERSUASIF PT. BUMI MEKAR HIJAU DALAM MENGURANGI KEBAKARAN HUTAN DESA RIDING SUMATERA SELATAN MELALUI PROGRAM DESA MAKMUR PEDULI API - Lintang Arum Bagasatu; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Forest fires was a crisis for Indonesia in 2014-2015 ago. Many parties feel the impact directly. The fires are caused by nature and human activities. To reduce forest fires, PT. Bumi Mekar Hijau as a company engaged in HTI implement a program that aims to reduce forest fires caused by humans. The program is called the Desa Makmur Peduli Api (DMPA) program. This program is implemented inDesaRiding because Desa Riding participated in forest fire case. In the implementation of the program conducted persuasive communication so that people who become the goal can act as expected. The purpose of this study is to look at the credibility of persuasive, persuasive messages, selected communications media and the effects of persuasive communications conducted.This research uses qualitativedescriptive research method. Technique determine research subject by using purposive technique. Informant in this research is Chairman of Forest Protection Team PT. Bumi Mekar Hijau, Fire Marshal, Fire Brigade Team, DMPA Companion, Community Development and Desa Riding Sumatera Selatan Community. Data collection techniques are interview, observation, documentation. To achieve the validity of data in this study the authors use the extension of participation and triangulation.The results of this study indicate that PT. Bumi Mekar Hijau conducts persuasive communication in the process of implementing the DMPA program to aim to reduce forest fires. Communicators delivering persuasive communication messages to Desa Riding community have credibility, seen from the aspect of expertise where each individual involved in the messaging process already has good experience in the field of fire and socialization to the public and persuader from PT. Bumi Mekar Hijau can be trusted by Desa Riding Community. Messages delivered in the form of verbal messages that have aspects of clarity, simple and accuracy. To reinforce the contents of verbal messages are also used nonverbal messages. The media used are print media such as stickers and posters. DMPA program gives effect to Riding Village community, people start thinking about the benefits of DMPA program in terms of environment and economy, people have a sense of care for the forest and participate in preventing forest fires. The community also helped to extinguish the fire in case of forest fires. in addition to the assistance provided by the community has started to take advantage of the assistance provided by the company although not as a whole.Keyword: Communication, Persuasive, Communication peruasive, Fire, Forest, Forest Fire